THE ANALYSIS OF BUSINESS DIGITIZATION IMPACT THROUGH ONLINE PLATFORM ON BUSINESS STABILITY IN THE POST-PANDEMIC ERA - Muhammad Fachrul Salam; Andi Tenri Pada; Ainina Istiqomah; Annaf Saniyyah Zubeidi (Universitas Islam Negeri Alauddin Makassar, 2023)
The pandemic has also dramatically changed the way we live our lives, including how we shop. many MSMEs are taking advantage of online platforms such as e-commerce and online food delivery services in the hope of helping sell products online and reach a wider audience. This research has obtained an observable concept that how the impact of digitization in the context of variable service fees and data security on online platforms can affect business stability. This research was conducted using quantitative and qualitative data. Quantitative data in this study were obtained through various information and data from MSMEs, as well as the results of questionnaires for MSMEs. The research sample is 100 SMEs in 15 sub-districts in Makassar City. The research was conducted using a purposive sampling method, namely MSMEs that were established at least in early 2020 so that they could provide information about conditions during the pandemic and before the pandemic. Digitalization has a very significant impact on MSMEs, especially in the context of service fees and data security on online platforms in this post-pandemic era. It is important to remember that the impact of high online platform service fees will vary between businesses and sectors. Better data security has also been implemented by online platforms. therefore, a careful analysis of costs, security, and a suitable digitization strategy is essential in maintaining business stability.